PENGARUH MODEL COLLABORATIVE CREATIVITY LEARNING DENGAN METODE OUTDOOR STUDY TERHADAP KEMAMPUAN BERPIKIR SPASIAL SISWA - Putri Windrayani, Sheila Mei; Astutik, Sri; Nurdin, Elan Artono; Mujib, Muhammad Asyroful; Susiati, Ana (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2025)
Learning will continue to experience dynamic development. Based on observations, geography learning still does not emphasize spatial cognitive aspects and learning tends to be passive. This research aims to examine the significant influence of the collaborative creativity learning model using the outdoor study method in geography subjects on spatial thinking abilities. The research method used was quasi-experimental and designed with a posttest only control group design. The results of the research show that there is a significant influence of the use of collaborative creativity learning with the outdoor study method in geography subjects on spatial thinking abilities in the experimental class given the treatment, it is known that the independent sample T-test value is below (<) 0.05. The posttest on students' spatial abilities in the experimental class showed higher results compared to the control class.